How to make a milk market: A case study from the Ethiopian highlands - Holloway, G.J.; Nicholson, C.; Delgado, Christopher L.; Staal, Steven J.; Ehui, Simeon K. (International Livestock Research Institute, 2000)
Some smallholders are able to generate reliable and substantial income flows through small-scale dairy production for the local market; for others, a set of unique transactions costs hinders participation. Co-operative selling institutions are potential catalysts for mitigating these costs, stimulating entry into the market, and precipitating growth in rural communities. Trends in co-operative organisation in East African dairy are evaluated. Empirical work focuses on alternative techniques for effecting participation among a representative sample of peri-urban milk producers in the Ethiopian highlands. The techniques considered are a modern production practice (crossbred cow use), a traditional production practice (indigenous cow use), three intellectual-capital-forming variables (experience, education and extension) and the provision of infrastructure (as measured by time to transport milk to market). A Tobit analysis of marketable surplus generates precise estimates of non-participants distances to market and their reservation levels of the covariates measures of the inputs necessary to sustain and enhance the market. Policy implications focus on the availability of crossbred stock and the level of market infrastructure, both of which have marked effects on participation, and, inevitably, the social returns to agro-industrialisation.